2020
DOI: 10.1038/s41598-020-72353-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel targets identified by integrated proteomic and phosphoproteomic analysis in spermatogenesis of swamp buffalo (Bubalus bubalis)

Abstract: To understand mechanisms of spermatogenesis, the proteome and the phosphoproteome in prepubertal and pubertal swamp buffalo (Bubalus bubalis) testes were analyzed using tandem mass tag (TMT) coupled with liquid chromatography-tandem mass spectrometry (LC–MS/MS). In prepubertal testes, 80 proteins were overexpressed, 148 proteins were underexpressed, and 139 and 142 protein sites had higher and lower phosphorylation, respectively, compared to the levels in pubertal testes. Several of these proteins were associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In addition, they showed that retinoic acid, directly involved in spermatogenesis developmental transitions [ 34 , 40 ], can anticipate the expression of TRIM36 early on culture (day 8) [ 41 ]. Further, differential proteomics and phosphoproteomics in buffalo, comparing pre-pubertal and pubertal testes, demonstrated that TRIM36 is upregulated with age suggesting a role in the spermatogenesis process in this species [ 42 ]. Furthermore, Trim36 null mouse-derived spermatozoa showed lower total and progressive motility and less complex motility patterns [ 27 ].…”
Section: Trim36 Is Involved In Spermatogenesismentioning
confidence: 99%
“…In addition, they showed that retinoic acid, directly involved in spermatogenesis developmental transitions [ 34 , 40 ], can anticipate the expression of TRIM36 early on culture (day 8) [ 41 ]. Further, differential proteomics and phosphoproteomics in buffalo, comparing pre-pubertal and pubertal testes, demonstrated that TRIM36 is upregulated with age suggesting a role in the spermatogenesis process in this species [ 42 ]. Furthermore, Trim36 null mouse-derived spermatozoa showed lower total and progressive motility and less complex motility patterns [ 27 ].…”
Section: Trim36 Is Involved In Spermatogenesismentioning
confidence: 99%
“…Further, proteomic and phosphoproteomic analysis of prepubertal and pubertal testis of swamp buffalo identified ACTL7B to be higher abundant and phosphorylated in the pubertal testis, again suggesting a role in spermatogenesis (Huang et al, 2020). Single nucleotide polymorphisms in the coding sequence of ACTL7B in infertile men have been reported, however not been directly correlated to male infertility (Tanaka et al, 2007, Tanaka et al, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, a study comparing two groups of Luzhong mutton sheep with different fecundity identified nine genes, among these ACTL7B (and ACTL7A), which were associated with reduced litter size (Tao et al, 2021). Further, proteomic and phosphoproteomic analysis of prepubertal and pubertal testis of swamp buffalo identified ACTL7B to be higher abundant and phosphorylated in the pubertal testis, again suggesting a role in spermatogenesis (Huang et al, 2020). Single nucleotide polymorphisms in the coding sequence of ACTL7B in Development • Accepted manuscript infertile men have been reported, however not been directly correlated to male infertility (Tanaka et al, 2007, Tanaka et al, 2019.…”
Section: Introductionmentioning
confidence: 99%